Competence is The Criterion for Running for Syndicat Delegate Elections Under Law 02-23 - Mellouk, Mahfoud (Journal of Human Sciences, 2024)
The law related to the exercise of trade syndicat rights in 2023 introduced new conditions regarding the election of syndicat representative. This study aims to assess the impact of these conditions on the quality and effectiveness of syndicat work. Through an analytical approach, it has been determined that these conditions, as a whole, require further elaboration and clarification. This can be achieved through the issuance of executive decrees that outline the nature and type of training, as well as the required union, academic, and professional qualifications for candidacy.